Anthropometric Indicators as Predictors of Adiposity and Cardiometabolic Diseases (Global Journal of Medical Research, 2023)
Objective To evaluate the ability of anthropometric indicators to identify adiposity and metabolic syndrome MS in patients with arterial hypertension AH Materials and Methods Cross-sectional study with patients of both sexes age 20 years with AH and overweight and in outpatient care Lifestyle clinical and anthropometric data were collected and the following indicators were calculated body mass index waist-to-height ratio WHtR and conicity index CI Results A total of 181 patients 53 3 12 6 years participated There was a predominance of women 69 6 adults 69 1 patients with obesity 81 2 and sedentary lifestyle 79 0